In vitro and in vivo evaluation of doxycycline‐chondroitin sulfate/PCLmicrospheres for intraarticular treatment of osteoarthritis. Issue 6 (28th October 2014) - Aydin, Ozlem; Korkusuz, Feza; Korkusuz, Petek; Tezcaner, Aysen; Bilgic, Elif; Yaprakci, Volkan; Keskin, Dilek
Abstract Osteoarthritis (OA) is a degenerative joint disease, which has no complete treatment with medication yet. Intraarticular hyaluronan (HA) injection can decrease pain and modify the natural course of OA. This study was designed to provide long term delivery of an MMP (matrix‐metalloproteinase) inhibitor agent‐doxycycline, together with matrix regenerative agent‐chondroitin sulfate for treating OA which progress with matrix degenerations. Doxycycline (D) and doxycycline‐chondroitin sulfate (D‐CS) loaded poly‐ɛ‐caprolactone (PCL) microspheres (MS) were prepared as intraarticular delivery systems. Bio‐effectiveness of developed microspheres was first evaluated with three‐dimensional in vitro model of OA where both MS showed significant reduction in MMP‐13 levels compared to untreated OA‐chondrocytes at 15 and 24 days. Significant decrease was observed in GAG release into the media for both D MS and D‐CS MS treated groups at 15 and 24 days. Second, the microspheres were injected to rabbit knee in hyaluronan (HA) to evaluate the effectiveness of the treatment. Radiographic scores of D MS and D‐CS MS groups improved after 8 weeks when compared to OA group. Mankin‐Pitzker histological scores similarly showed improvement with D MS and D‐CSMS groups when compared to OA group. Ex vivo hardness tests of cartilages demonstrated superior hardness values with both doses of D‐CSMS compared to OA group. D MS showed promising improvement of OA in histology results. Although, both MS groups had similar effects on cells in the in vitro model, D‐CSMS had a positive contribution on all in vivo treatment outcomes and showed potential as a new strategy for treatment when applied to OA knee joints. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1238–1248, 2015.